Using Singing Method Assisted by Popular Children's Song Application in Mufrodat Learning - Ridha Rahmatannisa; Nurul Wahdah; Muhammad Redha Anshari; Marsiah Marsiah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
This study aims to determine the mufrodat memorization ability using the singing method assisted by the Popular Children's Song Application. Fifteen children aged 7-10 years participated in this study to take part in the "I Love Arabic" program in the Sukamulya Village, Palangka Raya, Central Kalimantan. A quantitative approach with a pre-experimental research method was used. Data were collected through tests, observation, and documentation. Descriptive statistical data analysis by presenting the average and N-Gain was used. The results showed that average of the pretest